Multi-library union, promoting ILL/DD of the Chinese science digital library. Issue 4 (21st November 2016) - Xi, Qingkui; Mao, Liju; Zhang, Bin; Shi, Wen; Bao, Ping
Abstract : Purpose: This study aims to describe and analyse interlibrary loans and document delivery (ILL/DD) in the Chinese Academy of Sciences and to evaluate the ILL/DD service quality of one particular library. Design/methodology/approach: ILL/DD at the Chinese Science Digital Library (CSDL) is described. The success of ILL/DD at CSDL is analysed. Finally, the service quality of one library's ILL/DD based on LibQUAL+ is evaluated. Findings: ILL/DD at CSDL can be improved through a multi-library union, and a modified LibQUAL+ model can be used to evaluate a library's ILL/DD service quality. Social implications: More patrons can access a better service, and the work efficiency of librarians can be improved. Originality/value: This study is helpful to librarians interested in ILL/DD and resource sharing in China.